Adaptive environmental assessment and management: a new approach to environmental impact assessment - Jones, Michael L.; Greig, Lorne A. (New directions in environmental impact assessment in Canada, 1985)

Adaptive Management of Renewable Resources - Walters, C. J. (Macmillan Publishers Ltd, 1986)
The author challenges the traditional approach to dealing with uncertainty in the management of such renewable resources as fish and wildlife. He argues that scientific understanding will come from the experience of management as an ongoing, adaptive, and experimental process, rather than through basic research or the development of ecological theory. The opening chapters review approaches to formulating management objectives as well as models for understanding how policy choices affect the attainment of these objectives. Subsequent chapters present various statistical methods for understanding the dynamics of uncertainty in managed fish and wildlife populations and for seeking optimum harvest policies in the face of uncertainty. The book concludes with a look at prospects for adaptive management of complex systems, emphasizing such human factors involved in decision making as risk aversion and conflicting objectives as well as biophysical factors. Throughout the text dynamic models and Bayesian statistical theory are used as tools for understanding the behavior of managed systems. These tools are illustrated with simple graphs and plots of data from representative cases. This text/reference will serve researchers, graduate students, and resource managers who formulate harvest policies and study the dynamics of harvest populations, as well as analysts (modelers, statisticians, and stock assessment experts) who are concerned with the practice of policy design.

Integrating blueprint and process: A structured flexibility approach to development management - Brinkerhoff, Derick W.; Ingle, Marcus D. (Public Administration and Development, 1989)
Managing socio-economic development according to highly detailed pre-implementation plans rigidly applied has not had a high degree of success in generating sustained progress in the world's poorer nations. At the other end of the spectrum is the process approach that avoids specifying targets in advance, and concentrates upon building problem-solving capacity among the people involved. Many international donor and developing country agencies favour the blueprint model, despite its performance weaknesses, for its control and specificity. The process approach is limited by its lack of fit with agency procedures and incentives. This article discusses a structured flexibility approach to development management that integrates the blueprint model's planned structuring of action with the process model's flexibility and iterative learning orientation. This blend provides the basis for the programmatic and financial accountability required to obtain support from donor and developing country bureaucracies, and facilitates adaptive management to deal with uncertain and changing task environments. Case examples from the Caribbean, Portugal, and Pakistan illustrate the application of the structured flexibility approach.
Keywords: IMPORTANT

Review of Development Projects as Policy Experiments: An Adaptive Approach to Development Administration - Uphoff, Norman (Economic Geography, 1985)

Development Projects as Policy Experiments: An Adaptive Approach to Development Administration - Rondinelli, Dennis A. (Methuen, 1983)
International assistance programmes for developing countries are in urgent need of revision. Continuous testing and verification is required if development activity is to cope effectively with the uncertainty and complexity of the development process. This examines the alternatives and offers an approach which focuses on strategic planning, administrative procedures that facilitate innovation, responsiveness and experimentation, and on decision-making processes that join learning with action. A useful text for academics and practitioners in development studies, geography and sociology.

The process approach to projects - ODA (Overseas Development Administration, 1989)